Fatigue Life Analysis of FSO Mooring Chain by Considering the Effects of Offloading Load - Shidqi, Hafizh Muhammad Naufal; Syahroni, Nur; Rosyid, Daniel Mohammad; Cahyaningtyas, Dewinta Putri (International Journal of Marine Engineering Innovation and Research, 2025)
Mooring chains are critical components in the maritime industry used to secure ships and floating oil and gas platforms such as FSOs to stay in their designated positions. The loads exerted on mooring chains during routine operations and additional loads during offloading operations can cause structural fatigue. Therefore, fatigue life analysis of mooring chains is essential to ensure safety and optimal performance. This study aims to conduct fatigue analysis of mooring chains by considering an important factor, namely the influence of offloading. Offloading load refers to the additional load exerted on the mooring chain during loading and unloading operations. The mooring system configuration uses a spread mooring system of 8 chains (4x2), 87 mm in diameter, with 20% pretension. In the fatigue analysis, the "Palmgren-Miner" method was used to evaluate the accumulated damage caused by cyclic loads. Then, the "Rainflow Counting" method is used to identify and count the number of load cycles that occur so that later the fatigue life can be calculated and known. From the research results, it was found that the mooring system configuration design still meets the safety factor requirements recommended by API RP 2 SK both during SLS, ULS, and FLS analysis. In SLS and ULS conditions, the greatest tension value is when the FSO is in the Ballast load condition, with the maximum value of tension that occurs is 2207.4 kN in SLS conditions, and 4151.6 kN in extreme conditions. In the FLS condition analysis, it was found that with an offloading frequency of 24 times per year (1271.89 hours), in the design configuration, the influence of the offloading system can increase up to 7% of the fatigue damage that occurs, and the lowest fatigue life, reduced by 3 years. The least fatigue life occurs in Chain 1.2 at the splash zone segment, which is 67 years.